What are the fundamental structures of concurrency?: We still don't know! - Abramsky, S (Elsevier, 2006)
Process algebra has been successful in many ways; but we don't yet see the lineaments of a fundamental theory. Some fleeting glimpses are sought from Petri Nets, physics and geometry.